Effects of Urban Development Patterns on Municipal Water Shortage - Heidari, Hadi; Arabi, Mazdak; Warziniack, Travis; Sharvelle, Sybil (Frontiers in Water, 2021)
While urban areas are being threatened by water shortage due to climate change and rapid population growth, effects of urban development patterns on future municipal water shortage are rarely investigated. We address this aspect of urbanization by assessing the impacts of sprawl versus high-density patterns on future changes in the sub-annual water shortage intensity-duration-frequency (IDF) relationships. The City of Fort Collins, Colorado, water supply system is chosen as a representative region that is rapidly developing over the last decades. The future water supply is estimated using the Soil and Water Assessment Tool (SWAT) driven with a hot-dry climate model from the statistically downscaled Coupled Model Intercomparison Project, phase 5 (CMIP5) projections. Future water demand is projected using the Integrated Urban Water Model (IUWM) under both sprawl and high-density development patterns. The demonstration study reveals that urban areas under the sprawl development pattern are likely to experience water shortage events with higher intensity, duration, and frequency compared to the high-density pattern. Characterizing impacts of urban development patterns on future water shortage conditions is required for sustainable water management and smart urban growth and can help urban planners and water managers to develop an adaptive path to meet future water demand and decrease the vulnerability of municipal water supply systems to shortage.